Le numérique au service de la transmission du savoir-faire artisanal. Méthodes et outils numériques d’apprentissage du savoir gestuel de la poterie - Sotiris MANITSARIS (Tic & Société, 2017)
The tangible cultural heritage is the result of high level know-how, acquired and transmitted over centuries within local communities through the association of gestural intelligence and the creativity of the human spirit. However, this know-how is currently threatened by globalization and industrialization, due in particular to the devaluation of manual work and the difficulty of “boxing up” this gestural expertise, of recording and codifying it so that it can be transmitted across generations. This article presents an overview of existing methods and tools and proposes a new strategy for know-how transmission based on motion capture and gesture recognition technologies.